Becoming Muslim in Imperial Russia - Kefeli, Agnès Nilüfer.
1 online resource (313 pages)
Keywords: Kefeli shows how traditional education, with Sufi mystical components, helped to Islamize Finno-Ugric and Turkic peoples in the Kama-Volga countryside and set the stage for the development of modernist Islam in Russia.